Early human kinship : from sex to social reproduction - Allen, Nicholas J. (Wiley-Blackwell, 2011)
Sponsored by the Royal Anthropological Institute, in conjunction with the British Academy, Early Human Kinship brings together original studies from leading figures in the biological sciences, social anthropology, archaeology, and linguistics to provide a major breakthrough in the debate over human evolution and the nature of society